Penerapan Media Poster untuk Meningkatkan Motivasi Belajar pada Mata Pelajaran Akidah Akhlak - Badriah, Ida Nurul; Saefuddin, Asis; Muhamadi, Sani Insan (Mitra PGMI: Jurnal Kependidikan MI, 2021)
This research was motivated by the lack of student motivation in the subject of Akidah Akhlak. It was because learning activities were only lecture method and more teacher-centered so it affected students' motivation. The purpose of this study was to determine students' learning motivation before and after the implementation of poster media as well as to examine the process of learning Akidah Akhlah at grade III MI Hayatul Islam Cileat Subang. This research was a Classroom Action Research consisted of two cycles. The results showed that students' learning motivation before using poster media was still lacking (31.5%). The implementation of poster run based on its stages, the activities of teachers and student have increased in every cycle. In the first cycle, the teacher's activities reached 82.3% and then increased in the second cycle by 97.1%. Meanwhile, students' learning activities in the first cycle reached 76.4% and then increased in the second cycle by 91.1%. Therefore, students' learning motivation after using poster media has increased, in the first cycle the mean score reached 48.7 and then increased in the second cycle by 68.3 (good).